Nilai-Nilai Agama Hindu Yang Terkandung Dalam Cerita Maha Prastanika Parwa - Dewa Ketut Hendra Puspawan (Genta Hredaya: Media Informasi Ilmiah Jurusan Brahma Widya STAHN Mpu Kuturan Singaraja, 2020)
The Maha Prastanika Parwa story is part of the Mahabharata. The Maha Prastanika Parwa story has an influence on intellectuals and community leaders who view this story from a philosophical point of view, because this story contains the values of moral  in a form that is staged directly to the conscience of the community, because this story can be used as a guide in a community life. This research is in the form of a qualitative design with a phenomenological approach. Data were collected using interview techniques and literature techniques. After the data was collected, the data were analyzed using an interpretive approach. Based on this analysis, the following conclusions are obtained as a result of the research: (1) The story structure contained in the Maha Prastanika Parwa story includes plot, theme, setting, characterization and mandate. (2). The concept of Hindu theology contained in the Maha Prastanika Parwa story is that the value of leadership is a basic concept of wisdom that must be used as a basis for wisdom that must be used as a basis for action by leaders, Ethical values are good and noble behavior in accordance with the provisions of Dharma and Yadnya, and the value of tattwa is something that emphasizes us on a good deed.